Incidence of new onset arrhythmia after non cardiac surgery - Rajbhandari, Rajib; Shah, Jageshwar Prasad; Pradhan, Arya; Dangol, Rebika; Dangol, Utsav; Manandhar, Ashreyata; Banskota, Bibek; Baidhya, Niraj; Bajracharya, Tamanna (Journal of Advances in Internal Medicine, 2023)
BACKGROUND Although new-onset arrhythmia are a common problem in cardiothoracic surgery, their incidence in major non- cardiac surgery has not been studied properly. The aim of the study is to assess the incidence of arrhythmia after non cardiac surgery. While we have some data on postop arrhythmia after general surgery, we don’t have much data on orthopedic surgery, and good proportion of our patient in the study belong to this category. Thus it is also aimed to compare the incidence of arrhythmia in different types of surgery. METHODOLOGY The present study is a retrospective cohort of 100 patients who recently underwent surgery between 2023 January 1st till 2023 June 1st. All included patients were monitored in ICU and post-operative ward after surgery. 100 patients (28 female and 72 male) without any history of prior arrhythmia were analyzed and included in the study. Incidence of postoperative arrhythmia (PA) was observed and compared in patients undergoing different types of surgery. Impact of age factor on the incidence of PA was also studied. RESULTS Incidence of overall PA among all patients were 31%. Incidence of significant PA were 14.3%. Incidence of significant PA was highest in gastro-surgery patients (22%) whereas orthopedics patients had 11% incidence of PA. CONCLUSION Gastro surgery seems to give high impact on incidence of PA. In our analysis, age of the patient appear to be associated with the causation of PA.